2002
DOI: 10.1053/ajkd.2002.30558
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and energy metabolism in chronic renal insufficiency

Abstract: Malnutrition and wasting are important determinants of morbidity and mortality in patients with chronic renal failure on dialysis. The aim of this study was to determine body composition and energy metabolism in patients with chronic renal insufficiency before dialysis. We compared 15 patients (9 women and 6 men) with chronic renal failure (creatinine, 1.5 to 4.2 mg/dL) with 15 normal subjects pair-matched for sex, age (renal failure versus normal, 71 +/- 3 years versus 64 +/- 3 years), height (1.61 +/- 0.02 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 29 publications
2
51
1
5
Order By: Relevance
“…In fact, Passey et al (2003) measuring the total energy expenditure and the dietary intake of predialysis patients following a conventional low protein diet found the majority of patients would meet their energy expenditure at 126 kJ/kg/day (30 kcal/kg/day) rather than the recommended 146 kJ/kg/day (35 kcal/kg/day). Moreover, some evidence for lower resting energy expenditure compared to healthy subjects has been recently demonstrated (O'Sullivan et al, 2002;Avesani et al, 2003). Additionally, in our study the maintenance of the nutritional status even with low energy intake could be the result of a higher protein intake as demonstrated by PNA.…”
Section: Discussionsupporting
confidence: 63%
“…In fact, Passey et al (2003) measuring the total energy expenditure and the dietary intake of predialysis patients following a conventional low protein diet found the majority of patients would meet their energy expenditure at 126 kJ/kg/day (30 kcal/kg/day) rather than the recommended 146 kJ/kg/day (35 kcal/kg/day). Moreover, some evidence for lower resting energy expenditure compared to healthy subjects has been recently demonstrated (O'Sullivan et al, 2002;Avesani et al, 2003). Additionally, in our study the maintenance of the nutritional status even with low energy intake could be the result of a higher protein intake as demonstrated by PNA.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, the profound abnormalities in cell metabolism that occur in renal failure (Om and Hohenegger, 1980) and the impaired energy metabolism of skeletal muscle caused by circulating uremic toxins (Conjard et al, 1995) may be additional factors contributing to reduce REE in renal failure patients. Accordingly, studies with CKD patients not yet on dialysis have recently demonstrated lower REE than healthy pair-matched controls (O'Sullivan et al, 2002;Avesani et al, 2004b). In HD patients evaluated in a nondialysis day, a recent study showed that protein breakdown and oxidation was considerably reduced compared with control subjects, suggesting lower metabolic activity in this patient group (Veeneman et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Posteriormente, trabalhos com objetivo semelhante, mas que empregaram metodologia mais adequada (grupos pareados por sexo e idade, e ajuste do GER pela massa corporal magra) mostraram resultados diferentes [15][16][17] . Na fase não dialí-tica da DRC, um estudo que avaliou o GER de indivíduos idosos (n=15, idade 60 anos) mostrou que ele se encontrava reduzido quando comparado ao de idosos saudáveis 17 .…”
Section: Gasto Energético De Repouso Na Doença Renal Crônicaunclassified
“…Na fase não dialí-tica da DRC, um estudo que avaliou o GER de indivíduos idosos (n=15, idade 60 anos) mostrou que ele se encontrava reduzido quando comparado ao de idosos saudáveis 17 . Corroborando esse achado, Avesani et al 18 , ao analisarem o GER de indivíduos com DRC em tratamento conservador em uma amostra maior (n=45) e com idade mais abrangente (33 a 56 anos), também encontraram o mesmo resultado.…”
Section: Gasto Energético De Repouso Na Doença Renal Crônicaunclassified